2015
DOI: 10.1136/bjsports-2015-094982
|View full text |Cite
|
Sign up to set email alerts
|

Professional Rugby Union players have a 60% greater risk of time loss injury after concussion: a 2-season prospective study of clinical outcomes

Abstract: AimTo investigate incidence of concussion, clinical outcomes and subsequent injury risk following concussion.MethodsIn a two-season (2012/2013, 2013/2014) prospective cohort study, incidence of diagnosed match concussions (injuries/1000 h), median time interval to subsequent injury of any type (survival time) and time spent at each stage of the graduated return to play pathway were determined in 810 professional Rugby Union players (1176 player seasons).ResultsMatch concussion incidence was 8.9/1000 h with ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 27 publications
6
129
3
Order By: Relevance
“…al. noted similar findings among professional rugby players, with the incidence of any injury for players who returned to play in the same season following a diagnosed concussion being 60% higher compared to non-concussed players [14]. Finally, Pietrosimone et.…”
Section: Introductionmentioning
confidence: 66%
“…al. noted similar findings among professional rugby players, with the incidence of any injury for players who returned to play in the same season following a diagnosed concussion being 60% higher compared to non-concussed players [14]. Finally, Pietrosimone et.…”
Section: Introductionmentioning
confidence: 66%
“…39 However, the results and odds ratios are highly consistent with the limited previous findings relating concussion and subsequent musculoskeletal injury. 9,11,28,36,39 Concussion self-report is inherently limited by the honesty and accuracy of the respondents but has previously demonstrated moderate to high reliability. 24,32 The instrument herein has been previously utilized and demonstrated high test-retest reliability (0.92), but the study is limited by the presumption of accurate responses and interpretation of the questions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, soccer players also had an elevated injury risk in the year prior to concussion. 11,36 Similarly, a Swedish hospital database also identified an elevated injury risk in the 2 years prior (1.98× elevated risk) or after (1.72× elevated risk) a diagnosed concussion. 9 Most recently, 2 tightly controlled prospective studies of collegiate student-athletes identified a 1.6 to 2.5 times elevated risk of subsequent lower extremity injury postconcussion.…”
mentioning
confidence: 99%
“…Typically, the time to RTP after concussion is shorter than for the majority of other injuries. The average time taken for professional rugby players to return after concussion in the Cross study3 is 11 days compared to an average of 21 days for musculoskeletal injury in the same cohort 5…”
Section: Possible Mechanisms For the Increased Risk Of Musculoskeletamentioning
confidence: 99%
“…Three recently published studies on professional soccer players,1 American college athletes2 and professional rugby players,3 have all identified an increased risk of injury following RTP after concussion. In addition, although not statistically significant, a further study highlighted a trend for concussed Australian rules footballers to have twice the rate of injuries of matched non-concussed players on RTP 4.…”
Section: Increased Injury Risk Following Rtpmentioning
confidence: 99%